Microbial metabolites and heart failure: Friends or enemies? - Lu, Xiaofeng; Liu, Jingjing; Zhou, Bing; Wang, Shuwei; Liu, Zhifang; Mei, Fuyang; Luo, Junxiang; Cui, Yong (Frontiers in Microbiology, 2022)
Heart failure (HF), a global health issue characterized by structural or functional cardiac dysfunction, which was found to be associated with gut microbiome recently. Although multiple studies suggested that gut microbiome may had an impact on the development of cardiovascular diseases, the underlying mechanism of gut microbiome in HF remains unclear. The study of metabolites from gut microbiota influenced by dietary nutrition uptake had suggested that gut microbiota may affect the process of HF. However, on the basis of microbiota’s complicated roles and their interactions in metabolites, studies of microbial metabolites in HF had rarely been described so far. In this review, we focused on dietary nutrition related factors which was involved in the development and progression of HF, such as trimethylamine N-oxide (TMAO), short-chain fatty acids (SCFAs) and bile acids (BAs), to summarize their advances and several potential targets in HF. In addition, from a therapeutic standpoint, we discussed microbial metabolites as a potential strategy and their applications in HF as well.